Application of Genomic In Situ Hybridization (GISH) and tandem repeat sequence amplification for identification of Erianthus – Saccharum introgression - Valiya Purakkal Sobhakumari; Krishnasamy Mohanraj (Caryologia)
In our experiment a F1 hybrid (GU (04)-28-EO2) obtained from Erianthus procerus (IND 90-776) x Saccharum officinarum (PIO 96-435) was crossed with a commercial variety, Co 06027. Resulted BC1 hybrid (GU 12-25) was crossed with a commercial cane Co 12009. From this cross ten BC2 progenies were selected and analysed for introgression of Erianthus genome into Saccharum. F1 resulted from 2n+n chromosome transmission and was having the whole 40 chromosomes of E. procerus in it. The BC1 and BC2 resulted from n+n transmission. The introgression of E. procerus chromosomes into BC2 ranged from 8-10. Amplification of Erianthus specific tandem repeat (ESTR) sequences was successfully utilized in identification of genuine hybrids of E. procerus x Saccharum. No recombination events between Erianthus X Saccharum could be observed in F1, BC1 and BC2 clones. The current study forms a basis for targeted introgression breeding with a different unexploited species of Erianthus, E. procerus in sugarcane improvement programme.